Construction of punctured polar codes based on genetic algorithm - Mueadkhunthod, Krittiyaporn; Min Myint, Lin Min; Supnithi, Pornchai; Phakphisut, Watid (My University, 2021)
In this work, we propose a new construction of punctured polar codes, which provides a good error-correcting performance at arbitrary code lengths and code rates. We exploit the density evolution to evaluate the error probability of punctured polar codes. Then, the puncturing pattern and frozen bit positions are selected by genetic algorithm to construct a punctured polar code with low error probability. The results show that the proposed technique provides superior block error rate performance than the quasi-uniform puncturing technique at a high code rate. At a low code rate, the proposed technique can show the better performance than the shortening technique.
Keywords: Density evolution; Genetic algorithm; Polar code; Puncturing; Shortening